Meningkatkan Hasil Belajar Peserta Didik Melalui Metode Mind Mapping Pada Mata Pelajaran Pendidikan Agama Islam - Abdul Rouf; Abdul Kholiq (Research Journal on Teacher Professional Development, 2023)
Student learning outcomes are achievements achieved by students academically through exams and assignments, activeness in asking and answering questions that support the acquisition of these learning outcomes. One of the elements that support the success of learning is to determine the right method related to the material being studied. The method used to determine the increase in participant learning outcomes here is to use the mind mapping method. This research is used to find out how to increase student learning outcomes after going through the mind mapping strategy. This study shows that the use of the mind mapping method is proven to be able to improve student learning outcomes, especially in PAIBP subjects. This proof can be used as a comparison material for learning in other subjects with other themes in order to get even more valid results.